2009
DOI: 10.1002/j.2161-1912.2009.tb00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Japanese International College Students' and U.S. College Students' Mental‐Health‐Related Stigmatizing Attitudes

Abstract: this study examined differences between japanese international college students and u.s. college students on stigma toward people with psychological disorders, stigma tolerance in help seeking, and self-concealment. japanese international students had greater stigma toward individuals with psychological disorders than did their u.s. counterparts. no interrelationships between these variables, however, were found in the japanese international student group. este estudio examinó las diferencias entre estudiantes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 24 publications
1
35
0
3
Order By: Relevance
“…As discussed elsewhere (Corrigan and Penn 1999;Link and Phelan 2001;Link et al 1999), mental health stigma is pervasive, and greater mental health stigma is associated with less favorable help-seeking attitudes (Leong and Zachar 1999;Masuda et al 2009b;Vogel et al 2005). Masuda and colleagues (Masuda et al 2009a) found that Asian American college students, regardless of help-seeking history, had greater mental health stigma and less favorable help-seeking attitudes than European American students.…”
mentioning
confidence: 96%
“…As discussed elsewhere (Corrigan and Penn 1999;Link and Phelan 2001;Link et al 1999), mental health stigma is pervasive, and greater mental health stigma is associated with less favorable help-seeking attitudes (Leong and Zachar 1999;Masuda et al 2009b;Vogel et al 2005). Masuda and colleagues (Masuda et al 2009a) found that Asian American college students, regardless of help-seeking history, had greater mental health stigma and less favorable help-seeking attitudes than European American students.…”
mentioning
confidence: 96%
“…However, the converse appears to be true as well. Masuda et al (2009) sampled American college students and found that those who hid their problems or were more negative toward people with mental health problems were also more likely to hold stigmatizing beliefs toward receiving help. Their finding mirrors the results of this research, which indicated that students who are concerned about other people knowing if they had a mental illness were more likely to report stigmatizing attitudes, including being uncomfortable around people with mental illness, being afraid of people with mental illness, believing people with mental illness are not smart enough for most jobs, and being less likely to seek treatment for their own mental health needs.…”
Section: Discussionmentioning
confidence: 98%
“…Research has demonstrated that the attitudes and beliefs of mental health professionals toward clients can have a direct effect on the quality of the worker-client relationship and service out comes (Eack & Newhill, 2008;O'Connell & Stein, 2011;Scheyett & Kim, 2004;Schulze, 2007). Negative attitudes toward and low expectations of seriously mentally ill clients limit the abilities of professionals to develop effective working partnerships with those clients (Bentley, Farmer, & Phillips, 1991).…”
Section: Worker-client Relationshipsmentioning
confidence: 97%
“…Self-stigma was found to be negatively associated with intention to seek help among college students (Wade et al, 2011). Masuda et al (2009) found that Japanese international students, compared with US college students, reported having greater stigma toward individuals with psychological disorders. Miville and Constantine (2007) studied cultural values, counseling stigma, and intentions to seek counseling among Asian American college women.…”
Section: Subjective Norms and Perceived Behavioral Controlmentioning
confidence: 98%